1968
DOI: 10.1021/jf60159a024
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution of protein by solubility classes in the milled rice kernel

Abstract: Radial distribution of the four solubility classes of protein was determined for eight varieties of milled rice. Five consecutive layers of the kernel, totaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…Albumin content of total protein was higher in the sub-aleurone layer than in the inner endosperm, in agreement with Houston et a/. 29 The proportion of globulin in the protein of sub-aleurone was higher than that in the inner endosperm protein only in the high-protein rice. Based on these results, the crystalline protein bodies and the small spherical protein bodies present only in the sub-aleurone layer'3 together probably have the same aminogram as the common large spherical protein bodies.…”
Section: Proteinsupporting
confidence: 88%
“…Albumin content of total protein was higher in the sub-aleurone layer than in the inner endosperm, in agreement with Houston et a/. 29 The proportion of globulin in the protein of sub-aleurone was higher than that in the inner endosperm protein only in the high-protein rice. Based on these results, the crystalline protein bodies and the small spherical protein bodies present only in the sub-aleurone layer'3 together probably have the same aminogram as the common large spherical protein bodies.…”
Section: Proteinsupporting
confidence: 88%
“…However, polishing increased the glutelin concentration in PTT1 and CNT1, increased prolamin concentration in KDML105 and CNT1, but depressed the prolamin concentration in KLG1 and PTT1. Work undertaken by Cagampang et al (1966), Houston et al (1968), and others suggest that storage protein types are not evenly distributed across the grain, with albumin and globulin more abundant in the outer region of the grain (including the aleurone layers) and glutelin increasing in proportion toward the center of the endosperm. By contrast, prolamin is more evenly distributed across the endosperm.…”
Section: Discussionmentioning
confidence: 99%
“…The major storage proteins found in rice are the glutelins, which according to previous studies, account for 80% or more of the total seed protein (Tecson et al, 1971;Juliano, 1972;Villareal and Juliano, 1978). The remaining 20% is divided as follows: albumins, 1 to 5%; globulins, 4 to 15%; and prolamines, 2 to 8% (Houston et al, 1968). It has been demonstrated that the relative contributions of each of the solubility classes of seed proteins can be influenced by genotype, growing conditions, and the analytical methods employed (Sugimoto et al, 1986;Ogawa et al, 1987;Huebner et al, 1990).…”
mentioning
confidence: 98%